Low Carbon Transition Technical, Economic and Policy Assessment - Silva, Valter; Hall, Matthew; Azevedo, Inês (IntechOpen, 2018)
Most leaders of developed nations recognize the importance of following policies and strategies to achieve a low-carbon economy based on new and innovative technologies that are able to reduce greenhouse gas emissions and create new employment and growth. In the broad spectrum of the feasible decarbonisation pathways, the challenge for political and economic decision-makers is to weigh uncertain impact from different technologies and to build a comprehensive evidence-based framework for research, business, investment and policy decision-making. This book aims to provide the reader with a comprehensive overview of the current state-of-the-art technology in the Low Carbon Technology and Economy field, discussing a set of new technology approaches and environmental and economic implications.